Surgical treatment and outcome of early invasive adenocarcinoma of the uterine cervix (FIGO stage IA1). Issue 2 (21st April 2017) - Yahata, Hideaki; Sonoda, Kenzo; Yasunaga, Masafumi; Ohgami, Tatsuhiro; Kawano, Yoshiaki; Kaneki, Eisuke; Okugawa, Kaoru; Kaku, Tsunehisa; Kato, Kiyoko
Abstract: Aim: To investigate the surgical outcome of FIGO stage IA1 cervical adenocarcinoma. Methods: Between 2005 and 2011, 12 patients from Kyushu University Hospital had cervical adenocarcinoma, with a tumor depth of less than 3 mm and a horizontal width of less than 7 mm (FIGO stage IA1), diagnosed by cervical conization. All patients underwent simple hysterectomy or simple trachelectomy with pelvic lymphadenectomy. Results: The mean patient age was 34 years (range, 26–70 years). The median follow‐up period was 70.5 months (range, 26–99 months). No pelvic lymph‐node metastasis was seen, and no patient experienced disease recurrence. Conclusion: Early invasive cervical adenocarcinoma with a depth of invasion of 3 mm or less and a horizontal spread of 7 mm or less has little potential for nodal metastasis or recurrence. Therefore, simple hysterectomy or trachelectomy, without lymphadenectomy, might be an alternative treatment option for stage IA1 cervical adenocarcinoma.